APPLICATION OF ULTRAVIOLET (UV) TECHNOLOGY ON WATER DECHLORINATION: INFLUENCE OF UV FLUENCE DOSE AND UV TRANSMITTANCE ON CHLORINE REMOVAL EFFICIENCY - Maryani Paramita Astuti; Xie Rongjing (President University, 2016)
Water dechlorination is required to remove chlorine residual (free and combined chlorine) formed as byproducts of chlorination treatment. Ultraviolet (UV) dechlorination method has advantages compared to other dechlorination methods. This method uses a powerful photon energy generated by low pressure (LP) and medium pressure (MP) UV lamps to break chemical bond of the residual chlorine into reactive free radicals (•OH−) and (•Cl −). Studies are needed to evaluate its removal efficiency and the effect of treatment conditions on the efficiency before applying this method to practical applications. This study evaluates the effectiveness of medium pressure UV technology on UV dechlorination and investigates the influence of operation conditions (UV fluence and UV Transmittance) on chlorine removal efficiency. The impacts of both UV fluence and UV transmittance variations on chlorine removal efficiency were observed. Results of this study indicate that chlorine reduces upon exposure of UV radiation and chlorine removal efficiency increases with the increasing of UV fluence dose and UVT. The maximum UV fluence dose applied in this study (513 mJ/cm2) results in less than 25% of total chlorine reduction.